What networks of attention are affected by depression? A meta-analysis of studies that used the attention network test - Nidhi Sinha; Swasti Arora; Priyanka Srivastava; Raymond M. Klein (Journal of Affective Disorders Reports, 2022)
Background: Depression is an all-too-common mood disorder that has been linked in various ways to the cognitive concept of attention. The Attention Network Test, based on the influential taxonomy of attention originally proposed by Posner, can be used to measure the efficacy of three components or networks of attention: Alerting, Orienting and Executive Control. Our focus here is to discover how depression might affect these networks. Methods: Studies related to attention and depression were selected for this meta-analytic review using the online Attention Network Test (ANT) Database (Arora, Lawrence & Klein, 2020) resource. Based on the inclusion and exclusion criteria, 5 publications were analyzed with a Bayesian hierarchical model to compare participants with and without a diagnosis of depression. Results: The posterior distribution of our model revealed no credible differences in the Alerting and Orienting networks but showed credible non-zero values for Executive Control. This suggests that Executive Control is less efficient in individuals suffering from depression. Limitations: As literature using the ANT with depressed participants is limited, the methodological variability between studies in this meta-analysis should be considered when interpreting these results. Conclusion: This meta-analysis review is the first quantitative review that aimed to address the ANT-depression literature. A consistent finding of no alerting and no orienting deficit but a deficit in the executive control suggests that some, but not all, components of attention are impaired in depression.